The impact of external environment on the internal thermal environment of the main prayer of Putra Mosque, Putrajaya - Mohamad Ariff, Atikah Syahirah; Mat Husin, Noer Ezzati Balqis; Abu Bakar, Aniza; Hj Mohd Ariffin, Noor Aziah (2012)
Designing the outdoor landscape in hot and humid climate requires a deep understanding as it has a significant impact on the internal environment of a building. The rise in air temperature normally affects the energy consumption for cooling the internal environment of building. In order to mitigate this issue, bioclimatic design is crucially needed to be integrated as it may enhance the comfort conditions. A thermally comfortable external environment may consequently contribute positively on the internal environment. This paper seeks to explore the impact of the landscape design with focus on ground surface materials on the microclimate of the external environment, and the thermal effect on the main prayer hall of Putra Mosque. The orientation of the mosque, adjacency to a huge water body and an open plaza is among factors considered for this study. Among the methods used in this study include the measurements of thermal environment variables such as air temperature, relative humidity, solar radiation and wind speed. Hence, by studying these aspects, suitable landscape design recommendations could be predicted to create conducive thermal environment.